2022
DOI: 10.1136/bmjophth-2022-001079
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mutational landscape of genes associated with inherited retinal disease using large genomic datasets: identifying loss of function intolerance and outlying propensities for missense changes

Abstract: BackgroundLarge databases permit quantitative description of genes in terms of intolerance to loss of function (‘haploinsufficiency’) and prevalence of missense variants. We explored these parameters in inherited retinal disease (IRD) genes.MethodsIRD genes (from the ‘RetNet’ resource) were classified by probability of loss of function intolerance (pLI) using online Genome Aggregation Database (gnomAD) and DatabasE of genomiC varIation and Phenotype in Humans using Ensembl Resources (DECIPHER) databases. Genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 45 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…Many ocular tumour-associated-genes, when haploinsufficient, are strongly associated with negative selection. In contrast, we have previously shown that for IRDs, relatively few genes were associated with negative selection for loss of function variants 9. It should be noted that many of these ocular tumour-associated-genes develop their mutations as somatic mutations.…”
Section: Discussionmentioning
confidence: 76%
“…Many ocular tumour-associated-genes, when haploinsufficient, are strongly associated with negative selection. In contrast, we have previously shown that for IRDs, relatively few genes were associated with negative selection for loss of function variants 9. It should be noted that many of these ocular tumour-associated-genes develop their mutations as somatic mutations.…”
Section: Discussionmentioning
confidence: 76%
“…Haploinsu ciency in PRPF31 is a well-established mechanism in the pathogenesis of RCD [20], [21] , [22]. The majority of PRPF31 mutations result in null alleles, leading to haploinsu ciency and subsequent photoreceptor death in the retina [20], [21]. This mechanism is responsible for the incomplete penetrance of the disease phenotypes associated with PRPF31 variations [20].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue-specific RAE and BAE thresholds were defined using the same Z-score cutoff for body tissue and brain tissue. Loss-of-function intolerance was determined by cross-referencing our dataset with the dataset from Tanner et al, 2022 [8]. We evaluated the molecular and biological pathways that are significantly enriched using the GO knowledgebase (http://geneontology.org/, accessed on 7 July 2023) (http://pantherdb.org/, accessed on 7 July 2023) for both hc-BAE and hc-RAE genes [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…Recent work has developed new methods to reveal RAE genes and has generated large, open-source datasets of RAE and biallelic expression (BAE) genes [7]. Our study used this dataset, in concert with other datasets [8] and publicly available genetics resources, including the Gene Ontology (GO) knowledgebase [9,10], to define the roles of RAE and BAE among IRDs.…”
Section: Introductionmentioning
confidence: 99%